Spectra of magnetic chain graphs: coupling constant perturbations. (4th March 2015) - Exner, Pavel; Manko, Stepan S
Abstract: We analyze spectral properties of a quantum graph in the form of a ring chain with a δ coupling in the vertices exposed to a homogeneous magnetic field perpendicular to the graph plane. We find the band spectrum in the case when the chain exhibits a translational symmetry and study the discrete spectrum in the gaps resulting from changing a finite number of vertex coupling constants. In particular, we discuss in detail some examples such as perturbations of one or two vertices, weak perturbation asymptotics, and a pair of distant perturbations.